Design of Application for Calculating Human Resources for Medical Record Technician with ABK-Kes using the Excel Macro - Fery Fadly; Dhiya Ulhaq (Jurnal Mantik, 2022)
Distribution of medical record technicians in several health service institutions still not in accordance with the workload in each division, and calculation of human resource needs for medical record technicians was still calculated manually. The calculation of ABK-Kes will be faster and easier to do if there is a system or application that can help the calculation process. The purpose of this research is to design an application for calculating human resources for health using ABK-Kes method in the medical records section at the hospital. The type of research is qualitative research with a prototype system development method. Data collection methods that used are interviews, document review and literature study. The research results are start from communication and analyzing system requirements, rapid design, prototype development, evaluation, and improvement of prototypes, to produce an application for calculating the human resource needs of medical records based on VBA macro excel. Conclusion of research is the application has been adapted to the ABK-Kes method and can operate well so it can help the medical record technicians in calculating the human resource needs faster and easier.